Hermenêutica jurídica fenomenológica - Penteado Filho, Hélio de Negreiros (2022)
The present work bring us a legal hermeneutics through the phenomenological method proposed by Edmund Husserl, from an intuitive concept of law as the search for the just and justice. For that, under the phenomenological philosophical vector, it traces back a critical history of legal hermeneutics from the historical school of law and its developments until the break of phenomenology with the Cartesian reason of the cogito to enable access to a new horizon of legal interpretations of entities